2008
DOI: 10.1243/09544062jmes835
|View full text |Cite
|
Sign up to set email alerts
|

Singular properties of flow separation as a real cause of cavitation inception

Abstract: At the very beginning stage of cavitation an infinitesimal cavity suddenly emerges and rapidly grows on the wall close to the point of flow separation. The present paper intends to make clear the mechanism of this peculiar phenomenon previously discovered by the present authors in oil flows, by experimentally examining the characteristics of a separating flow. First, pressure and temperature distributions along a cylindrical smooth wall in an oil flow were measured across the point of separation, which has pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…For the purpose, various kinds of methods have been adopted to research the development of cavitation in hydraulic machineries, including numerical simulations and experimental investigations. [2][3][4][5][6][7][8] With the development of cavitation, Tsujimoto et al divided the process of cavitation into cavitation surge, rotating cavitation, and asymmetric cavitation, and explained the mechanisms of the phenomenon, as well as the characteristics of those instabilities caused by cavitation, based on two-dimensional stability analyses. [9][10][11] The most common method used to identify the presence of cavitation was based on the observations of the drop in head and 3% head drop from noncavitation was regarded as the critical cavitation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the purpose, various kinds of methods have been adopted to research the development of cavitation in hydraulic machineries, including numerical simulations and experimental investigations. [2][3][4][5][6][7][8] With the development of cavitation, Tsujimoto et al divided the process of cavitation into cavitation surge, rotating cavitation, and asymmetric cavitation, and explained the mechanisms of the phenomenon, as well as the characteristics of those instabilities caused by cavitation, based on two-dimensional stability analyses. [9][10][11] The most common method used to identify the presence of cavitation was based on the observations of the drop in head and 3% head drop from noncavitation was regarded as the critical cavitation.…”
Section: Introductionmentioning
confidence: 99%
“…For the purpose, various kinds of methods have been adopted to research the development of cavitation in hydraulic machineries, including numerical simulations and experimental investigations. 28…”
Section: Introductionmentioning
confidence: 99%
“…A large tensile strain rate near the valve port causes cavitation when the poppet moves to the lowest valve lift. 21 In addition, the cavitation at the valve port appears although the vibration amplitude of poppet is small with a flow rate of 2.4–3.0 L/min in experiment of N-S21-F15; this is because the valve cavity pressure is higher due to the larger flow rate. In the experiment of N-S21-B10, the valve cavity pressure is higher than 3.2 MPa when the flow rate is greater than 3.0 L/min, and due to the higher pressure, the cavitation occurs at the end of the valve port.…”
Section: Experimental Phenomena and Analysismentioning
confidence: 96%
“…Washio 2022 used a high-speed camera to observe the flow in the hydraulic valve. It was found that the periodic shedding of the bubble at the valve port caused the same period pressure fluctuation of the hydraulic valve.…”
Section: Introductionmentioning
confidence: 99%
“…The inception of cavitation is commonly associated in the literature 25 to a nuclei which fills with vapor when it experiences a pressure drop below the liquid vapor pressure. Washio, Takahashi, and Yoshimori, 26 Washio et al, 27 and Washio, Kikui, and Takahashi 28 observed vaporous cavitation inception in viscous mineral oil separated flows and proposed another inception mechanism which does not depend on the presence of a nuclei. According to their studies, vapor cavities can emerge close to a separation point on the wall where the liquid undergoes high tensions which can, when the threshold is exceeded, induce a microscopic rift between the liquid and the wall leading to the emergence of a cavity.…”
Section: Introductionmentioning
confidence: 98%